OPTIMIZATION OF ELECTRONIC DOCUMENT EXCHANGE SYSTEMS USING QUANTUM ALGORITHMS (American Journal of Technology and Applied Sciences, 2024)
This paper explores the optimization of electronic document exchange systems through the application of quantum algorithms. We investigate the potential of quantum computing to enhance the efficiency, security, and speed of these systems. The study includes mathematical modeling, simulations, and comparative analysis of classical and quantum approaches. Results indicate significant improvements in performance metrics, showcasing the viability of quantum algorithms in this domain.